COMPILATIVE-VERNACULAR TAFSĪR TARJUMĀN AL-MUSTAFĪD “Analysis of Sources, Methods, and Contextualization in Khazanah Islam Nusantara” - Fahrizal, Al; Khoiriyyah, Khofawati (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
Tarjumān al-Mustafīd, a monumental work by Abdur al-Rauf al-Sinkili, is the first complete Qur'anic exegesis in the Malay language and a milestone in the intellectual history of Southeast Asian Islam. This qualitative research comprehensively analyzes the book's sources, methods, and style through library research and content analysis. The results show that Tarjumān al-Mustafīd is not a translation but an original compilation-synthesis of various sources, including Tafsīr al-Khāzin, al-Bayḍawī, and al-Jalālayn. Its method combines ijmālī (global) and tahlīlī (analytical) approaches, making it accessible yet substantial. Its style is general, covering Ash'arī theology, Shafi'ī jurisprudence, and ethical Sufism. Its genius lies in the process of vernacularization that made the Qur'an relevant to the Malay community. In conclusion, this work is best described as a compilative-vernacular exegesis whose originality lies in its creative synthesis and brilliant contextualization for its local audience.